ANALISIS PERSEPSI DAN KETERLIBATAN KONSUMEN TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN DALAM TRANSAKSI E â COMMERCE - Tsaanii, Adiilah Adlan Ats; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The enhancement of public access to the Internet, particularly on a web commerce that provides a place to perform activities of online buying and selling or it is known as c2c such as facebook, Kaskus, OLX, Tokopedia,etc. this research is meant to analyze the influence of those four variables to the product purchasing decision through the web c2c commerce. The sample of this research is a person who has ever done product purchasing through websites of c2c commerce which has been obtained by using non-probability sampling technique. Moreover, the analysis to the data is obtained by using multiple regressions analysis. The analysis includes validity test and reliability test, classic assumption test, multiple regressions analysis, hypothesis test through t test and F test, as well as the coefficient determination analysis (R2). the result of t test indicates that these two variables of independent variables i.e. trust, and consumer involvement which have been studied have been proven to have significant influence to the dependent variable i.e. purchase decisions. Meanwhile, two of which service quality and ease does not have any significant influence on the dependent variable i.e. purchase decision. The result of the F test shows that all independent variables have significant influence to the purchasing decisions.Keywords: c2c commerce, purchasing decisions, trust, ease, service quality.